2019
DOI: 10.1002/ange.201904707
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenative Silylation of Alkenes for the Synthesis of Substituted Allylsilanes by Photoredox, Hydrogen‐Atom Transfer, and Cobalt Catalysis

Abstract: As ynergistic catalytic method combining photoredox catalysis,hydrogen-atom transfer,and proton-reduction catalysis for the dehydrogenative silylation of alkenes was developed. With this approach,ahighly concise route to substituted allylsilanes has been achieved under very mild reaction conditions without using oxidants.T his transformation features good to excellent yields,o perational simplicity, and high atom economy.B ased on control experiments, apossible reaction mechanism is proposed. Scheme 1. Strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The direct alkenylation of aldehydes represents a highly attractive and sustainable strategy for the synthesis of this important family of compounds. We were excited to find that various primary and secondary aldehydes were effective substrates under the optimal alkenylation conditions, providing α,β-unsaturated ketones in decent yields with exclusive E selectivity (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Notably, excellent site selectivity was observed for aldehyde C-H bonds, while other activated C-H bonds, such as benzylic (34), allylic (38), propargylic (39) and α-heteroatom C-H bonds (42 and 43), were not functionalized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct alkenylation of aldehydes represents a highly attractive and sustainable strategy for the synthesis of this important family of compounds. We were excited to find that various primary and secondary aldehydes were effective substrates under the optimal alkenylation conditions, providing α,β-unsaturated ketones in decent yields with exclusive E selectivity (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Notably, excellent site selectivity was observed for aldehyde C-H bonds, while other activated C-H bonds, such as benzylic (34), allylic (38), propargylic (39) and α-heteroatom C-H bonds (42 and 43), were not functionalized.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we were inspired by direct hydrogen atom transfer (HAT) photocatalysts that could achieve the straightforward activation of C-H bonds 33 decatungstate anion ([W 10 O 32 ] 4− ), a polyoxometalate photocatalyst that has been broadly applied in various functionalizations of alkanes and aldehydes [34][35][36][37][38][39] . On the other hand, photocatalytic dehydrogenative cross-coupling reactions with concomitant hydrogen evolution have recently been developed through cooperative photoredox and cobaloxime catalysis, as pioneered by the Wu and Lei groups [40][41][42][43][44] . Inspired by these studies, we proposed that the combination of decatungstate anion and a cobaloxime catalyst could enable the direct activation and alkenylation of alkanes and aldehydes using alkenes as the feedstocks.…”
mentioning
confidence: 99%
“…However, the substrates were invariably limited to phenylsilanes or (TMS) 3 SiH with labile Si-H bonds (Scheme 1b). 11,[29][30][31][32][33][34][35] As pioneered by Fagnoni et al, 36 decatungstate was found to be an effective hydrogen atom transfer (HAT) photocatalyst for aromatic tertiary silanes activation (Scheme 1c). Nevertheless, only poor selectivities were observed for trialkylsilanes owing to the comparably high bond dissociation energies (BDEs) of Si-H and α-Si-C-H bonds (>92 kcal mol −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that overoxidation of the products is inhibited by a rapid electron back transfer between the product and the photocatalyst. Other challenging dehydrogenative bond-forming reactions (e.g., C-N [64-66], C-O [64,67-69], C-P [70-72], C-S [62,73], C-Si[74]) by CCHE have also been reported, providing further evidence for the versatility of this strategy to construct C-heteroatom bonds.…”
mentioning
confidence: 99%